POWERS OF BINOMIAL EDGE IDEALS WITH QUADRATIC GRÖBNER BASES - ENE, VIVIANA; RINALDO, GIANCARLO; TERAI, NAOKI (Nagoya mathematical journal, 2022)
We study powers of binomial edge ideals associated with closed and block graphs.